Antimicrobial Activity of Tobacco Flower Extract (Nicotiana tabacum L.) in Various Solvent - Lina Oktavia Rahayu; Ernanin Dyah Wijayanti; Fajriana Ikra Pratidina; Vanny Sasmita Ayuningtyas (JSMARTech: Journal of Smart Bioprospecting and Technology, 2023)
Tobacco plants (Nicotiana tabacum L.) are known to contain secondary metabolites that function as antimicrobials. But thus far only the leaves, roots, and stems have been utilized. The research aimed to determine antimicrobial activity of tobacco flower extract in various solvent. The tobacco flowers were extracted used ethanol, methanol, and N-Hexane solvents. The extracts were tested for antimicrobial activity against Staphylococcus aureus and Candida albicans by dilution method. The results showed that ethanol and methanol extracts of tobacco flowers had a Minimum Inhibitory Concentration (MIC) value of 32% and a Minimum Bactericidal Concentration (MBC) of 64% against S. aureus and C. albicans. As for the N-Hexane extract of tobacco flowers, it has MIC value of 64% and MBC of 64% against C. albicans. In conclusion, tobacco flower extract in ethanol, methanol, and N-hexane solvent have potential functions as antimicrobial agents.